PENDIDIKAN DALANG BALI UTARA: STUDI KONSEPTUAL BISA DAN DADI DALAM PRAKTEK BELAJAR WAYANG BERBASIS LONTAR DHARMA PAWAYANGAN - Erman Risky Dewa Suprapta; Made Reland Udayana Tangkas; I Putu Ardiyasa (Pusat Penerbitan LP2MPP ISI Bali, 2026)
This research investigates the growing dissonance in North Balinese puppetry education, specifically the gap between technical proficiency ('bisa') and spiritual-ethical legitimacy ('dadi'). The dalang, traditionally a sacred figure guided by the Lontar Dharma Pawayangan, faces a pedagogical crisis as the holistic 'aguron-guron' (master-apprentice) system is supplanted by formal institutions prioritizing technical skills. This qualitative study, employing ethnographic methods and textual analysis, reveals that this shift leads to a perceived decline in 'taksu' (spiritual charisma) and a suboptimal implementation of the Dharma Pawayangan theo-aesthetic principles among younger puppeteers. To address this fragmentation, the study proposes a 'Tri-Pola Integrative Model' for puppeteer education. This model aims to synthesize the strengths of the three existing pillars to produce a complete puppeteer. This model synthesizes the strengths of three pillars: the Academic (formal institutions) as a theoretical foundation, a center for critical research, documentation, and analysis; the Community (sanggar) as a practical laboratory, an incubator for creativity, and a space for social interaction; and the Spiritual (Mpu/masters) as a vehicle for transmitting intangible elements such as taksu, ethics, and spiritual practices. By integrating John Dewey's philosophy of experiential learning and Talcott Parsons' AGIL framework for systemic sustainability, this model aims to produce a 'dalang paripurna' (a perfected puppeteer) who holistically embodies both 'bisa' and 'dadi', ensuring the vitality and sanctity of the tradition.